2011
DOI: 10.1080/13546805.2010.546074
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine administration in healthy volunteers reproduces aberrant agency experiences associated with schizophrenia

Abstract: Introduction. Aberrant experience of agency is characteristic of schizophrenia. An understanding of the neurobiological basis of such experience is therefore of considerable importance for developing successful models of the disease. We aimed to characterise the effects of ketamine, a drug model for psychosis, on sense of agency (SoA). SoA is associated with a subjective compression of the temporal interval between an action and its effects: This is known as “intentional binding”. This action–effect binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 55 publications
9
55
0
Order By: Relevance
“…Although unexpected, this finding has been replicated in subsequent patient studies (Voss et al, 2010). This hyper-binding effect has also been induced in healthy controls following infusion of the drug ketamine (Moore, Turner, Corlett, et al, 2011). Ketamine is an anaesthetic agent which acts as an NDMA-receptor antagonist.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…Although unexpected, this finding has been replicated in subsequent patient studies (Voss et al, 2010). This hyper-binding effect has also been induced in healthy controls following infusion of the drug ketamine (Moore, Turner, Corlett, et al, 2011). Ketamine is an anaesthetic agent which acts as an NDMA-receptor antagonist.…”
mentioning
confidence: 48%
“…Moore, Turner, Corlett, et al (2011) showed that intentional binding was significantly stronger in participants on ketamine compared with their own performance on a placebo. This replicates the hyper-binding found in patients with schizophrenia.…”
mentioning
confidence: 99%
“…Taken together, these data confirm that PE-driven inferences are central to a range of experiences. Ketamine and psychosis similarly perturb these PEs, and those perturbations relate to the severity of endogenous and ketamine induced psychotic symptoms (Moore et al, 2011b). …”
Section: Is Altered Pe Signalling Enough To Explain Delusions?mentioning
confidence: 99%
“…This strategy is exemplified by the use of the NMDA-receptor antagonist, ketamine, in challenge studies with patients (Lahti et al, 1995) and healthy volunteers (Krystal et al, 1994, 2003; Adler et al, 1999; Umbricht et al, 2000; Moore et al, 2011; Neill et al, 2011), to test the hypothesis that NMDA-receptor hypofunction contributes to both clinical symptoms and neurocognitive deficits in schizophrenia.…”
Section: Potential Solutions and Recommendationsmentioning
confidence: 99%